Scalable mesh partitioning for multibody-3D finite element based rotary-wing structures. (June 2023) - Lumba, Ravi; Datta, Anubhav
Highlights: Specialized mesh partitioner developed to partition complex multibody problems. Parallel solver developed to solve partitioned data structures. Linear speedup achieved up to 48 subdomains for practical rotary wing structure. Special mesh partitioner is necessary for meaningful speedup on complex problems. Skyline storage eliminates coarse problem barrier to parallel scalability. Abstract: This paper presents a new and specialized mesh partitioner for large-scale three-dimensional multibody rotor dynamic models. This partitioner enables parallel solution with modern domain decomposition algorithms of complex, multibody, three-dimensional finite element problems. A parallel solver using a state-of-the-art iterative substructuring algorithm, FETI-DP, is developed in this paper to solve the partitioned data structures. The main feature of the partitioner is the ability to robustly partition any generic multibody structure, although it has several special features for rotary-wing structures. The NASA Tilt Rotor Aeroacoustic Model (TRAM), a 1/4 scale V-22 model, was specially released by NASA as a challenge test case. This model contains four flexible parts, six joints, 18 composite material decks, a blade fluid–structure interface, and control angle inputs. The parallel solver scalability is studied for progressively increasing complexity, from the isolated rotor blade to the blade and hub assembly. The use of a skyline solver for the coarse problem is shown to eliminate the coarse problem barrier. The special partitioner features are demonstrated to enable efficient parallel solution and significantly improve the performance and scalability. The principle barrier of computational time that prevented the use of high-fidelity three-dimensional structures in rotorcraft is thus resolved.